Death after Sexual Intercourse. (1st December 2015) - Braun, Christian T.; Ricklin, Meret E.; Pauli, Andreina; Ott, Daniel; Exadaktylos, Aristomenis K.; Pfortmueller, Carmen A.
Abstract : Sexuality is an essential aspect of quality of life. Nevertheless, sexual intercourse is physically challenging and leads to distinct changes in blood pressure, heart, and respiratory rate that may lead to vital complications. We present a case report of a 22-year-old female suffering from subarachnoid hemorrhage after sexual intercourse. The patient was immediately transported to hospital by emergency medical services and, after diagnosis, transferred to a tertiary hospital with neurosurgical expertise but died within 24 hours. After postcoital headaches, subarachnoid hemorrhage is the second most common cause of neurological complications of sexual intercourse and therefore patients admitted to an emergency department with headache after sexual intercourse should always be carefully evaluated by cerebral imaging.